Logistic aspects of the planning of packaging - Telek, Péter (Advanced Logistic Systems - Theory and Practice, 2026)
The most dynamically developing service of our time is freight transport. Millions of small and large packages are delivered every day in different parts of the world, and we can send goods, packages and consignments from practically anywhere to anywhere. As the number of traditional mail items decreases, the desire to send packages increases in parallel, which results the increasing of the number of different freight transport companies. The transmission of goods requires the use of various packaging, against which serious expectations are placed on preserving the integrity of the goods and reducing transport costs. This article reviews the logistical aspects of packaging design, primarily from the perspective of selecting the optimal packaging from a logistical point of view.